Treatment landscape and burden of disease in metastatic castration-resistant prostate cancer: systematic and structured literature reviews - Leaning, Darren; Kaur, Gagandeep; Morgans, Alicia K.; Ghouse, Ray; Mirante, Osvaldo; Chowdhury, Simon (Frontiers in Oncology, 2023)
Metastatic castration-resistant prostate cancer (mCRPC) is a lethal disease that imposes a major burden on patients and healthcare systems. While much progress has been made developing therapies for mCRPC beyond taxane-based chemotherapy, particularly androgen receptor pathway inhibitors (ARPIs), their effectiveness is limited by the almost inevitable development of primary or acquired treatment resistance. The current lack of therapeutic options for patients with mCRPC means that it remains an incurable disease. The overarching aim of this systematic and structured literature review was to identify unmet needs for patients with late-stage mCRPC by broadening our understanding of the global disease burden from the patient and economic perspective, and exploring the current and emerging treatment landscape. We show that, while geographic differences exist, the overall disease burden of mCRPC is high, and there is a global need for affordable, tolerable treatment options with novel mechanisms of action that can improve survival and health-related quality of life in this difficult-to-treat population. Determining the optimal treatment sequencing to avoid cross-resistance between ARPIs is essential. We conclude that optimal management of patients with mCRPC mandates continued development of innovative treatments combined with a holistic approach that considers the patient's preferences and psychological and physical well-being.